ENGLISH TEACHING METHODS - Khurramova Mohinur Askar qizi (TADQIQOTLAR, 2026)
Abstract This article explores various English teaching methods, highlighting their principles, advantages, and limitations. It provides an overview of traditional and modern approaches, including the Grammar-Translation Method, Direct Method, Audio-Lingual Method, Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and the Natural Approach. Each method is analyzed in terms of its focus-whether on grammar, communication, repetition, or learner engagement-and suitability for different learning contexts. The article emphasizes the importance of adapting methods to learners’ needs and integrating multiple approaches to enhance language acquisition effectively.